Adaptive sliding mode controller design of Markov jump systems with time-varying actuator faults and partly unknown transition probabilities. (May 2018) - Yao, Deyin; Liu, Ming; Lu, Renquan; Xu, Yong; Zhou, Qi
Abstract: This paper addresses the stabilization problem of a class of Markov jump systems with time-varying actuator faults and partially known transition probabilities via the sliding mode control method. In this study, the exact information of the time-varying actuators faults, nonlinearities and external disturbances considered in this paper is unknown for the controller design. By Lyapunov stability theory, some sufficient conditions of stochastic stability for Markov jump systems in the existence of actuators faults, unknown nonlinearities and unknown perturbation are derived. Finally, the effectiveness of the proposed control method is illustrated by a simulation example.